INFORMATION SEEKING BEHAVIOUR OF MEDIA PROFESSIONALS IN KARACHI - Ansari, Munira Nasreen; Zuberi, Nisar Ahmed (Malaysian Journal of Library and Information Science, 2010)
The purpose of this study was to investigate the use of various information channels, the awareness of the existence of information sources, ways used for disseminating information and use of libraries among media professionals in Karachi. A questionnaire was used as an instrument for data collection for the survey. Data was gathered from 185 media professionals who belonged to three types of media houses (T.V, radio and newspaper). Findings indicate that library is the most used channel among newspaper professionals and television professionals. Reference service and newspaper clipping service are the most favorable information services in the library. Media professionals get to know of the information sources through common knowledge and review articles. Internet is the channel, which is being used increasingly by media practitioners; however use of Internet among newspaper practitioners is high as compared to radio and television practitioners. Quite surprisingly, the use of libraries among radio practitioners was found to be particularly low. All groups of the practitioners mentioned reading of book reviews published in newspapers to know the existence of an information source. This study would be helpful for librarians and information specialists, who are working in media house libraries for library planning and designing of library services in their parent organisation